The impact of users' trust on intention to use the mobile medical platform: Evidence from China - He, Jinjiang (Frontiers in Public Health, 2023)
The mobile medical platform, which is an effective supplement to offline medical service, can provide patients with a wider range of more convenient medical services and help solve the current public medical problem of shortage of medical resources. Although the existing medical service platform has gained widespread attention, its adoption rate and acceptance by the market have not yet reached a high level. How to increase the utilization rate of the mobile medical platform by users to relieve medical pressure has become an urgent issue to be discussed. This article attempts to build a research model of users’ use intention on the mobile medical platform based on the framework of “trust – intention” and introduces innovation acceptance and technical risk concerns as the two moderating variables. The main conclusions are threefold: (1) Users’ trust in the mobile medical platform will affect their use intention; (2) Users with high personal innovation acceptance will promote the relationship between trust and use intention; (3) Users who are more concerned about the risks of innovative technologies will weaken the relationship between trust and use intention. The main contribution can be summarized from two aspects. This research is theoretically helpful to extend the research of new product adoption to mobile medical platforms, and innovatively introduce personal innovation characteristics and technical risk concerns for discussion. In practice, this research explores the user’s intention from the perspective of personal innovation characteristics, and provides guidance for optimizing the product design of the mobile medical platform and attracting more users to join the platform.